2019
DOI: 10.1016/j.chiabu.2018.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Identifying maltreatment subgroups with patterns of maltreatment subtype and chronicity: A latent class analysis approach

Abstract: Maltreatment experiences are complex, and it is difficult to characterize the heterogeneity in types of maltreatment. Subtypes, such as emotional maltreatment, sexual abuse, physical abuse, and neglect commonly co-occur and may persist across development. Therefore, treating individual maltreatment subtypes as independently occurring is not representative of the nature of maltreatment as it occurs in children's lives. Latent class analysis (LCA) is employed herein to identify subgroups of maltreated children b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
86
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(101 citation statements)
references
References 83 publications
(161 reference statements)
14
86
0
1
Order By: Relevance
“…In accordance with a study based on a sample of adolescents in foster care (Rebbe et al, 2017), a low maltreatment class and a cumulative maltreatment class were found in the present study. This finding was also reported by studies examining other populations (Adams et al, 2016;Charak et al, 2018;Ford et al, 2010;Warmingham et al, 2019).…”
Section: Discussionsupporting
confidence: 87%
“…In accordance with a study based on a sample of adolescents in foster care (Rebbe et al, 2017), a low maltreatment class and a cumulative maltreatment class were found in the present study. This finding was also reported by studies examining other populations (Adams et al, 2016;Charak et al, 2018;Ford et al, 2010;Warmingham et al, 2019).…”
Section: Discussionsupporting
confidence: 87%
“…The observed variables were expected to be related in different ways to the participants' roles. In the psychological and medical literature, LCA has been largely applied in past and recent years [53][54][55][56][57][58][59][60][61]. Once the latent structure is identified, LCA allows entering other variables in the model as covariates that might influence the latent structure; these are called external variables.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies should also utilize self-report measures of child maltreatment. Additionally, the majority of youth who experience maltreatment will experience multiple types of abuse and neglect (Warmingham, Handley, Rogosch, Manly, & Cicchetti, 2019). Thus, measuring subtypes of maltreatment independently may not accurately capture the experience of child maltreatment.…”
Section: Discussionmentioning
confidence: 99%